Electrical properties of Ta2O5-doped TiO2 varistor ceramics sintered at low-temperature. Issue 7 (August 2015) - Gong, Yunyun; Chu, Ruiqing; Xu, Zhijun; Sun, Jiao; Chao, Fenxia; Ma, Shuai; Hao, Jigong; Li, Huaiyong; Li, Guorong
Abstract: TiO2 -based varistor ceramics doped with 0.25–1.00 mol% Ta2 O5 were prepared by the conventional solid state reaction technique at 1300 °C and the effects of Ta2 O5 substitution on their electrical properties have been studied. The results showed that the Ta2 O5 dopant played an important role in the formation of the grain boundary barriers. Good electrical properties with E 1 mA =14.9 V/mm, α =4.48, ε r =9.68×10 4, tan δ =0.36 were obtained for 0.50 mol% Ta2 O5 addition. These results indicate the 99.5 mol% TiO2 +0.50 mol% Ta2 O5 +2 wt% (0.723 mol% Bi2 O3 +1 mol% B2 O3 ) composition might be a suitable candidate for capacitor–varistor functional device.